Eugenics and the Nature-Nurture Debate in the Twentieth Century - Gillette, A. (Palgrave Studies in the History of Science and Technology, 2007)
Gillette shows that the sciences of sociobiology and evolutionary psychology were undergoing rapid development in the early Twentieth century. However, many of the early researchers in these sciences were also eugenicists. With the rise of behaviourism and the reaction against eugenics in the 1930s, any scientific claims that behaviour might be influenced by heredity were suppressed for ideological reasons.